Beerhouses, brothels and bobbies : Policing by consent in Huddersfield and the Huddersfield district in the mid-nineteenth century - Taylor, David (Book collections on Project MUSE., 2016)
Professor David Taylor has established a fine reputation for his books and articles on the history of policing in England. This new book on Huddersfield policing looks at the mid-nineteenth century and issues facing the local area in relation to policing a centre of West Riding textile production.